A priority list of occupational carcinogenic agents for preventative action in Australia - Renae C. Fernandez; Timothy R. Driscoll; Deborah C. Glass; Deborah Vallance; Alison Reid; Geza Benke; Lin Fritschi (Elsevier, 2012)
Abstract Objective: To develop a list of carcinogens to guide decisions on priorities for preventive action in Australian workplaces. Approach: The following criteria provided the assessment framework to establish a list of priority carcinogens: evidence of carcinogenicity using International Agency for Research on Cancer (IARC) criteria; use in occupational circumstances; and use in Australia industry. Literature from national and international agencies relating to carcinogens and industrial practice informed the assessment. Conclusion: The final priority list contained 38 established or probable carcinogenic agents that are present in Australian workplaces. Agents were grouped into the following categories: combustion products, inorganic dusts, organic dusts, metals, radiation, other industrial chemicals and non‐chemical agents. The priorities are based primarily on the potential for occupational exposure and evidence of use in Australian industry because there is imited information on the prevalence and level of exposure to occupational carcinogens in Australia. Implications: The priority list of agents can provide direction for future disease burden studies to establish the prevalence and levels of exposure to carcinogens amongst Australian workers. From a policy viewpoint, a priority list will allow regulators to focus on activities such as setting exposure standards and restricting importation and use.